Pengungkapan Proses Penganggaran Dana dan Akuntabilitas dalam Implementasi Dana Penerapan Corporate Social Responsibility (Studi pada PDAM Kabupaten Buleleng) - I Putu Tedy Arya Wahyudi; I Gede Agus Pertama Yudantara (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to find out how the process of budgeting Corporate Social Responsibility (CSR) funds at PDAM Buleleng Regency, to find out how the process of accountability of Corporate Social Responsibility (CSR) funds at PDAM Buleleng Regency, and to find out what are the obstacles faced in the disclosure process. budgeting and accountability of Corporate Social Responsibility at PDAM Buleleng Regency. This research method uses qualitative methods. The result of this research is that the budgeting process is regulated in the regional regulations of Buleleng Regency. Furthermore, the accountability of the budgeting process is shown by making financial reports that are checked by KAP and shown by the publication of social activities and CSR to the PDAM website. The results of the latest research from this study show that there are no obstacles in the budgeting process because there are regulations that regulate but in the realization process there are several problems due to the COVID-19 pandemic.